Launching an Electronic Patient-Reported Outcomes Initiative in Real-Time Clinical Practice. Issue 57 (3rd September 2021) - Palos, Guadalupe R; Suarez-Almazor, Maria E
Abstract: Patient-reported outcomes play an essential role in improving care across the cancer continuum. This paper reports on the experience of a tertiary care center to standardize the use, collection, and reporting of patient-reported outcomes (PROs) in 10 disease-specific survivorship clinics. To minimize the burden of patients to complete surveys, an institutional committee with oversight on all patient surveys required an application be reviewed and approved before their distribution in a clinic. To begin collecting PROs, each clinic submitted an application tailored to its clinical operations, staffing, and scheduling characteristics. The dates for the submission of each application were staggered over a 2-year period, which contributed to a lack of uniformity in the project (ie, approval dates, start dates, collection and reporting of results). The delays were primarily due to the time and resources required to build the electronic version of the PRO survey into the institutional electronic medical record. To date, 6 of 10 survivorship clinics submitted applications, 5 were approved, and 4 launched the electronic MD Anderson Symptom Inventory (eMDASI) through the patient portal. Metrics collected between January 2019 and December 2020 for the thyroid, bone marrow transplant, genitourinary, and head and neck clinics indicated the numbers of eMDASIs sent to patients varied by clinic, with the lowest from the bone marrow transplant survivorship clinic (6) and the highest (746) in the thyroid Clinic. The total number of eMDASIs returned by the patients ranged from 2 (bone marrow transplant) to 429 (thyroid). Overall, patients' return rates of the eMDASI ranged from 33.3% to 57.7%. Several strategies were implemented to increase the delivery, submission, and completion of eMDASIs. Our findings indicate the integration and implementation of PROs in survivorship clinics are achievable. Further work is needed to enhance the ePROs web-based process to adequately compare PROs across diverse cohorts of cancer survivors .